2019
DOI: 10.15171/jhp.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic potential of selected medicinal plant extracts in human whole blood cultures

Abstract: Introduction: Many plant-derived products despite wide usage are not scientifically evaluated for their safety and efficacy. Therefore, in the present study, we aimed to evaluate the cytotoxic and genotoxic activities of Polygonum aviculare L., Equisetum arvense L., Plantago lanceolata L. and Artemisia absinthium L. ethanolic extracts in human white blood cells. Methods: Cell viability was assayed by trypan blue exclusion method, while the genotoxicity was tested by cytokinesis-block micronucleus (CBMN) assay u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Interestingly, the lack of MN formation in cells treated with different concentrations of all the obtained extracts indicates the absence of genotoxic potential in all cases. These results are in accordance with previous findings in different biological models, such as human lymphocytes and Drosophila [ 53 , 55 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Interestingly, the lack of MN formation in cells treated with different concentrations of all the obtained extracts indicates the absence of genotoxic potential in all cases. These results are in accordance with previous findings in different biological models, such as human lymphocytes and Drosophila [ 53 , 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…Specifically, it has been reported that EtOH extracts of E. arvense L. demonstrated a dose-dependent decrease in the proliferation of human peripheral lymphocytes [ 32 ], and pancreatic carcinoma AsPC-1 cells [ 52 ]. Similarly, cell viability was significantly reduced in human blood cells treated with EtOH E. arvense L. extracts [ 53 ], while there is evidence that EtOH-W E. arvense L. extracts could be cytotoxic in A549 lung carcinoma cells [ 54 ]. Uslu et al [ 40 ], applying a response surface methodology to identify the optimal conditions for E. arvense L. extraction, reported that EtOH-W extracts, demonstrating high levels of AA and TPC, were highly cytotoxic against the NIH3T3 mouse fibroblast cell line, which was also revealed by the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations